Factores que motivan la decisión de uso de la bicicleta como medio de transporte cotidiano en un sector específico de Bogotá, D.C. (2019)
Recognizing Bogotá, D.C. as one of the Latin American cities with the largest number of bicycle trips, compared to the capitals of countries such as Argentina, Brazil, Chile, Mexico or Peru. The general objective is to determine the factors that motivate the users and non-users of a certain sector of the city of Bogotá, D.C., to use the bicycle as a means of daily transport. The methodology was descriptive, based on the application of a survey with a sample of 165 people who voluntarily agreed to answer it, with closed Likert questions and some open questions, whose instrument was statistically validated. In the sample there was a prevalence of women from the Usaquén locality in 36.84% compared to 26% of men. The results allowed us to identify safety, environmental, time saving, as well as health and personal care as motivating factors for the use of the bicycle. Those who tend to opt for the use of bicycles as a means of daily displacement between their place of residence and their workplace, belong to a young population under 40, with proximity in time and distance (average of 45 minutes and 20 km) from your residence to work, with very few or no person in charge, who does not use the private car in company, who does not prefer the bus or collective transport, Transmilenio and much less, the motorcycle, does not prefer the walk and shows inclination by individual means such as taxi or skateboard. It also has a cultural level that allows it to recognize the impacts and effects on personal health and the environment. The factors related to Facilities, Health, Safety and Times are classified as important or very important, unlike men.